2008
DOI: 10.1248/bpb.31.1079
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characterization and Mutational Analysis of the Recombinant Protein BWp16, a Major Allergen in Buckwheat

Abstract: Buckwheat allergy is one of the most critical diseases manifested by severe and dangerous symptoms in Japan and other countries. We previously isolated the cDNA encoding protein BWp16, a member of the 2S albumin family with a conserved motif of 8 cysteine (Cys) residues. Comparison of the deduced amino acid sequences of BWp16 and related proteins in the 2S albumin family showed similarities between BWp16 and BW 8-kDa from buckwheat, Ara h 6 from peanuts and Ric c 1 from castor bean. Purified recombinant BWp16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…We also demonstrated that ELISA using rBWp16 could be employed for in vitro diagnosis of buckwheat allergy [12]. In addition, we showed the involvement of cysteine residues in the allergenicity of BWp16 [12]. In the present study, we have identified a peptide as the linear IgE-binding epitope of BWp16, as well as the amino acid residues critical for IgE binding in BWp16.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…We also demonstrated that ELISA using rBWp16 could be employed for in vitro diagnosis of buckwheat allergy [12]. In addition, we showed the involvement of cysteine residues in the allergenicity of BWp16 [12]. In the present study, we have identified a peptide as the linear IgE-binding epitope of BWp16, as well as the amino acid residues critical for IgE binding in BWp16.…”
Section: Introductionmentioning
confidence: 53%
“…On the other hand, a 16-kDa protein has been reported to be resistant to pepsin digestion and to have IgE-binding activities with sera from patients with immediate hypersensitivity reaction to buckwheat [10]. Our previous studies have shown that the 16-kDa buckwheat seed storage protein (BWp16) is a strong candidate for the major buckwheat allergen involved in the 2S albumin family based on the character of the reaction between BWp16 and the sera of patients positive for IgE-binding activity to buckwheat [11,12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, recombinant allergens have become available for diagnostic and therapeutic purposes (23,30,31). It is particularly important to evaluate T cell activation for diagnosis and specific immunotherapy using allergens.…”
Section: Discussionmentioning
confidence: 99%
“…However, buckwheat can also cause allergy [5], and results in clinical symptoms including asthma, dermatitis, eczema, and even anaphylactic shock [6]. Since the first buckwheat-allergic patient was reported in 1909, buckwheat has been recognized as one of most important food allergens manifested by severe and dangerous symptoms induced by ingestion or inhalation of a small amount of the flour or food products [7]. The largest study on buckwheat allergy has been performed among 92,680 school children of Yokohama in the 1990s [8].…”
Section: Introductionmentioning
confidence: 99%